Financing Agriculture by Scheduled Commercial Banks in Punjab: Issues of Outreach - Trinath , Rayudu; Kataria, P. (Gyan Management Journal, 2009)
The present study has been undertaken to examine the status of financing agriculture in Punjab, with pecial reference lo the 011tread1 of lite Scheduled Commercial Banks (SCBs) vis-ii-vis location specificity of the branches. Primary and secondary data have been used for lite present study. The primary data has been collected from 14 rural, semi urban a11d i,rban branches of lite Punjab National Bank (PNB), selected ji-o,nfive districts of three climatic zones of Punjab. An effort has been made to present the comparative appraisal of fina11cial perfonnance of the SCBs operating in rural. semi-urbar, and urban locations of Punjab on the basis of profitability a11d liquidity status oftlte bra11ches. The aualysis co11clu.sively establishes lliat the rural bra11che.s cater to the demands of agricu/J.ural sector in a more efficient manner a.s compared to their semi-urban a11d urban counter parts.
Keywords: Credit; Agriculture; Outreach; Finanaal Performance; Scheduled Commercial Banks